PENGARUH PENERAPAN SISTEM MANAJEMEN SUMBER DAYA PERUSAHAAN (ERP) DALAM MENINGKATKAN KINERJA MANAJEMEN RANTAI PASOK (SCM) - Tan Phey Lien; Elvi Juriana; Cheristina Cheristina; Wenny Wenny; Evelyn Evelyn; Rizni Aulia Qadri (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
Application of Enterprise Resource Planning Systems (ERP) and Supply ChainManagement (SCM) systems by conducting research on one of the developingcompanies in Batam City. By implementing these two systems, it can have aninfluence on the implementation of ERP and SCM systems. The research methodused is a qualitative method with a descriptive approach. The results of the researchconducted illustrate that the SCM application system carried out by PT PanasonicIndustrial devices Batam has been designed in accordance with the systematics ofthe product distribution process. And in the application of ERP systems, PTPanasonic Industrial devices Batam is to use the Application and Product in DataProcessing (SAP) System. By empowering these two systems, PT PanasonicIndustrial devices Batam can provide performance in accordance with themanagement system that has been implemented.